ANALISIS MINAT MEMBACA SISWA KELAS RENDAH DI SDN BUNAJIH 2 LABANG - Husnul Jannah Alfauzah; Priyono Tri Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students' reading interest is an important aspect in literacy development and academic achievement. This study aims to analyze students' reading interest at SDN Bunajih 2 Labang. The results show that in general, the reading interest of low-grade students at SDN Bunajih 2 Labang is good, supported by student interviews, observations and teacher interviews. However, some students still show low interest in reading, which is in line with previous research findings on the correlation between reading interest and learning achievement. The school has implemented various strategies, including the CALISTUNG program and the reading corner, to increase students' interest in reading. Observational findings also revealed that reading corners are available in each classroom with a varied collection of books, used as learning resources and updated regularly. Nevertheless, there are some aspects that need to be improved, such as the management of the collection list and reading recap in the reading corner as well as improving communication between teachers and students. This research provides valuable insights for the development of more effective programs in improving students' interest in reading at SDN Bunajih 2 Labang and other schools.